Teatro poshistórico o en diferencia: ¿cómo se ha entendido el teatro posdramático? - Araque Osorio, Carlos (CALLE14: revista de investigación en el campo del arte, 2011)
﻿The article tackles a debate surrounding contemporary art in which the theories of drama are interconnected with other ways of understanding the performing arts. Classical theater—under the rule of the unities of time, space and action put forth by Aristotle— is brought into question, or at least reexamined, as the only way of assuming the theatrical happening. Postmodernity took essential steps towards the generation of new performing proposals, and the postdramatical allows for an ample and varied look upon drama; historical events areopposed to fictional events and there is no explicit fable. But the postdramatical may also fallin uncertainty. Its particular form of welcoming everything is its weak point. Theater is equated with performance art, the installation, the troupe, the marching band, juggling, the circus, and acrobatics, among other expressions which, even though they are related to the performing arts, are not theatrical events in the proper sense.